Profiling antibody epitopes induced by mRNA-1273 vaccination and boosters - Girard, Bethany; Baum-Jones, Elisabeth; Best, Rebecca L.; Campbell, Thomas W.; Coupart, Jack; Dangerfield, Kyla; Dhal, Abhilash; Jhatro, Michael; Martinez, Brian; Reifert, Jack; Shon, John; Zhang, Minlu; et al. (Frontiers in Immunology, 2024)
Background: Characterizing the antibody epitope profiles of messenger RNA (mRNA)-based vaccines against SARS-CoV-2 can aid in elucidating the mechanisms underlying the antibodymediated immune responses elicited by these vaccines.Methods: This study investigated the distinct antibody epitopes toward the SARS-CoV-2 spike (S) protein targeted after a two-dose primary series of mRNA-1273 followed by a booster dose of mRNA-1273 or a variant-updated vaccine among serum samples from clinical trial adult participants.Results: Multiple S-specific epitopes were targeted after primary vaccination; while signal decreased over time, a booster dose after >6 months largely revived waning antibody signals.Epitope identity also changed after booster vaccination in some subjects, with four new Sspecific epitopes detected with stronger signals after boosting than with primary vaccination.Notably, the strength of antibody responses after booster vaccination differed by the exact vaccine formulation, with variant-updated mRNA-1273.211 and mRNA-1273.617.2 booster formulations inducing significantly stronger S-specific signals than a mRNA-1273 booster.Overall, these results identify key S-specific epitopes targeted by antibodies induced by mRNA-1273 primary and variant-updated booster vaccination.